Participação e efetividade no Conselho Municipal da Criança e Adolescente : uma análise do ciclo de distribuição de recursos públicos em Guarapari-ES - Monteiro, Rhadson Rezende (2017)
In recent Democracy we have seen the creation of new representative spaces through participatory institutions. Give effective decision-making processes with the participation of civil society and operationalize the deliberation with effective implementation and result and the great challenge to improve the mechanisms of participatory democracy. This research is part of an academic effort to understand the dynamics of these new spaces in the search to give a point to a methodological study of these mechanisms, aiming to contribute to the construction of a Dialogical Public Administration. For this task, the study focuses on a specific type of participatory institutions, Municipal Council of Children and Adolescents of the Municipality of Guarapari, in a specific cycle of distribution of public resources for civil society organizations. It is a proposal that seeks to present an analysis of the effectiveness of results derived, mainly based on a legal, procedural, and institutional evaluation, aimed at public policy development actions, presented to the end to normative innovations that can improve this mechanism in Brazil From the promulgation of the Regulatory Framework of Civil Society Organizations